2005
DOI: 10.1093/rpd/nci303
|View full text |Cite
|
Sign up to set email alerts
|

The legacy of monazite processing in Brazil

Abstract: The exploitation of natural resources containing naturally occurring radionuclides may lead to enhanced levels of radioactive isotope and enhanced potential for exposure to naturally occurring radionuclides in products, by-products, residues or wastes. Such resources include, for instance, monazite, the processing of which, in Brazil, generated a great amount of radioactive residues, being stored in buried concrete tanks, in temporary storage buildings and in sealed trenches. In addition, during the 1980s ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…In these soils mitigation measures were adopted for remediation. It is observed that some values of the concentrations of 228 Ra and 226 Ra in soil samples from the radioactive anomaly of the cities of Pedra and Venturosa are within the range of values determined by Lauria and Rochedo [17]. This indicates that a more detailed study would be necessary to verify the possibility of mitigation measures for remediation in the soils existing in the locality of the radioactive anomaly of the Pernambuco and Pedra de Venturosa cities.…”
Section: Natural Radionuclides In Rocks and Soilsmentioning
confidence: 58%
See 1 more Smart Citation
“…In these soils mitigation measures were adopted for remediation. It is observed that some values of the concentrations of 228 Ra and 226 Ra in soil samples from the radioactive anomaly of the cities of Pedra and Venturosa are within the range of values determined by Lauria and Rochedo [17]. This indicates that a more detailed study would be necessary to verify the possibility of mitigation measures for remediation in the soils existing in the locality of the radioactive anomaly of the Pernambuco and Pedra de Venturosa cities.…”
Section: Natural Radionuclides In Rocks and Soilsmentioning
confidence: 58%
“…Soils contaminated with monazitic sand processing residues in the state of São Paulo, presented concentrations of 228 Ra and 226 Ra ranging from 153 to 33,000 and from 50 to 6,500 Bq.kg -1 , respectively [17]. In these soils mitigation measures were adopted for remediation.…”
Section: Natural Radionuclides In Rocks and Soilsmentioning
confidence: 99%
“…Lack of regulations related to radioactive wastes in Brazil led to radioactive wastes from monazite processing to be dumped without any protective measures. 83 Subsequent remediation of the sites resulted in additional waste that also had to be dealt with. These wastes could not be transported to other locations within Brazil as no one accepted them.…”
Section: Recycling Of Ree Magnetsmentioning
confidence: 99%
“…Attempts have been made to solve the problems resulting from the NORM wastes from the monazite cycle in Brazil and elsewhere, but to no avail [5][6][7]. One of the problems of the NORM wastes from the monazite cycle is bioavailability, which in the long run tends to have a distinct probability to reach the food chain.…”
Section: Data On Norm From the Monazite Cyclementioning
confidence: 99%